Role of thermal excitation in ultrafast energy transfer in chlorosomes revealed by two-dimensional electronic spectroscopy1. Issue 27 (21st July 2015) - Jun, Sunhong; Yang, Cheolhee; Kim, Tae Wu; Isaji, Megumi; Tamiaki, Hitoshi; Ihee, Hyotcherl; Kim, Jeongho
<x xml:space="preserve">Abstract</x> Two-dimensional electronic spectroscopy reveals the role of thermal excitation in excitation energy transfer in chlorosomes.